The Role of Data Analytics in Customer Behavior Analysis and Market Strategy Optimization (A Case Study) - Nusrat Fatima, Ayesha (International Journal of Information Technology and Computer Science Applications, 2025)
In the highly competitive global retail market, understanding customer behavior is essential for sustained business growth and strategic decision-making. Stellar Peak Sports & Adventure, a multinational retailer specializing in sports and outdoor products, is facing operational challenges due to a lack of deep customer insights. This deficiency has resulted in inefficiencies in marketing strategies, inventory management, and overall business performance. To address these issues, the company has enlisted the expertise of a business analyst to conduct a comprehensive customer analysis. This study employs a data-driven approach to identify and analyze key customer attributes, including demographic segmentation, purchasing behaviors, membership trends, and engagement patterns. The business analyst will determine the most relevant data sources, apply statistical and machine learning techniques to extract actionable insights, and develop interactive visualizations through a dashboard, enabling the company to monitor customer trends in real-time. Moreover, the study will critically assess potential risks associated with data analytics, such as data quality issues, biases in predictive modeling, and the challenges of integrating analytics into decision-making frameworks. Through a rigorous evaluation of customer data, this research provides strategic recommendations to optimize marketing campaigns, enhance customer segmentation, improve sales forecasting, and strengthen customer retention strategies. By leveraging advanced analytics, Stellar Peak Sports & Adventure can develop data-driven operational improvements, refine business strategies, and achieve a sustainable competitive advantage in the global sports and outdoor retail industry.